A fatal diarrhoea outbreak in farm‐raised Deinagkistrodon acutus in China is newly linked to potentially zoonotic Aeromonas hydrophila. Issue 1 (5th October 2018) - Liu, Junqi; Xie, Lingfeng; Zhao, Dun; Yang, Taotao; Hu, Yunfei; Sun, Zhiliang; Yu, Xinglong
Abstract: Deinagkistrodon acutus is a venomous pit viper commonly used in traditional Chinese medicine; farming these snakes has become a major industry. In 2017, an outbreak of fatal diarrhoea among farm‐raised D. acutus in Hunan Province caused the deaths of 5, 600 snakes within 3 weeks. We isolated a brand‐new sequence type of Aeromonas hydrophila (ST516) from lesions and confirmed that this bacterium was the causal agent of the outbreak. Snakes infected with the bacterium in the laboratory showed similar clinical symptoms to those of snakes in the original outbreak. We also tested bacterial virulence in Kunming mice to examine the likelihood of zoonosis. Isolates were pathogenic to mice, causing diarrhoea within 4 hr post‐challenge, which indicates that the bacterium can potentially infect mammals. Environmental analysis showed that polluted spring water likely caused the diarrhoea in snakes. This study is the first to report on a large‐scale outbreak of fatal diarrhoea in farm‐raised snakes, originating in a pathogen that can infect mammals. These results should raise awareness regarding potential anthropozoonosis among poikilotherms, mammals, and humans; appropriate prevention or control methods should be developed.